Enhancing recovery from plyometric circuit training: The synergistic impact of dynamic stretching, BCAA supplementation, and sports massage on DOMS - Fitrianto, Ari Tri; Prayoga, Hegen Dadang; Habibie, Muhammad; Fitrian, Zanzabil Adwa (Journal Sport Area, 2023)
Understanding the significance of efficient post-exercise recovery methods in alleviating muscle damage and addressing delayed onset muscle soreness (DOMS) among athletes following plyometric circuit training. The study aimed to determine the effect of dynamic stretching in water (active pool-based) and sports massage (SM) on muscle damage indices post-plyometric circuit training. A total of 30 participants were divided into three control groups and one experimental group, who were given two recovery protocols (APB + BCAA and sports massage) after the trial. Data were statistically analysed using a one-way ANOVA test with post-test measurements and a Bonferroni test (P < 0.05). It is concluded that statistically the APB + BCAA post-hoc test with SM did not show any significance. However, on average, APB + BCAA was preferable at reducing DOMS symptoms; measurements 3 and 4 in the intervention groups also showed a significant effect on the control group. The study findings underscore the valuable contribution of active recovery in water and the use of supplements in improving initial recovery outcomes after strenuous exercise or sports, aligning with the exercise recovery principle that highlights the inseparable relationship between nutrition and soft tissue modalities.